(untitled) (Ameghiniana, 2013)
A graptolite assernblage collected in the Ordovician sequence of Los Azules Formation, eastern slope ofthe Precordillera of San Juan is here described. The assernblage is composed of "Climacograptus" cf. "C". caudatus, Lapworth, "Climacograptus" sp., ? "Climacograptus" sp., "Amplexograptus" aff. "A." arctus (ElIes yWood), "Amplexograptus" minutus Cuerda, Cingolani, Schauer y Varela, Geniculograptus? cf. G. pygmaeus (Ruedmann) y "Glyptograptus angustifolius" (Hall). The Fossil bearing strata are refered to the Late Caradoc. These graptolites allow to establish an accurate correlation between the Caradoc levels of the Los Azules Formation with other Caradocian sequences of the Precordillera of the westem Argentina